The perspectives of volunteers with disabilities and sport event organizers on educating and employing volunteers with disabilities - Marlene Jobst; Christoph Kreinbucher-Bekerle (Frontiers in Sports and Active Living)
IntroductionInclusive sport events can increase the social inclusion of people with disabilities. While originally, people with disabilities are represented as athletes, they could also be a valuable resource volunteering at sport events. However, barriers to their inclusion exist due to a lack of accessibility at the event venue or missing knowledge of the event organizers about collaborating with people with disabilities. Training courses for volunteers with disabilities are rare but would help to integrate them at sport events. The present study reflects on the training course and the participants' implementation in different sport events.MethodsTherefore, six so called sport management assistants with disabilities (4 female and 2 male; age: M = 31.67; SD = 6.07) and five sport event organizers (3 female and 2 male; age: M = 41.20; SD = 9.04) were interviewed with a semi-structured guideline.ResultsThe feedback of both groups concerning their experiences was mainly positive. The training course prepared the sport management assistants with disabilities for their tasks at the sport events. The sport management assistant graduates were satisfied with their roles at the events but criticize the lack of accessibility. The organizers praised the enthusiastic workforces added to their teams and want to cooperate with volunteers with disabilities in future events.DiscussionThus, preparatory courses for people with disabilities as an educational tool should be encouraged to promote inclusion at sport events on a larger scale.